Development of green synthesis silver nanoparticle with Ocimum sanctum leaf extract: characterization and stability study - Martien, Ronny; Niswah, Sukma Uswatun; Kusumorini, Nindya (Majalah Farmaseutik, 2026)
This study aimed to synthesize, characterize, and evaluate the stability of silver nanoparticles (AgNPs) produced using Ocimum sanctum L. leaf extract through a green synthesis method. The aqueous extract of fresh basil leaves served as a natural reducing and stabilizing agent in the reduction of 1 mM silver nitrate solution at 80 °C, indicated by a color change from light yellow to brown. Phytochemical screening confirmed the presence of phenolic compounds, saponins, and flavonoids responsible for the reduction and stabilization processes. Characterization by UV–Visible spectrophotometry showed a surface plasmon resonance peak at 450 ± 4.93 nm, while particle size analysis indicated a Z-average of 85.77 ± 0.46 nm and a polydispersity index of 0.222 ± 0.003, reflecting uniform and monodisperse nanoparticles. The zeta potential of –14.23 ± 0.30 mV suggested moderate colloidal stability. After 30 days of refrigerated storage, the nanoparticles exhibited a red shift of the absorption peak, an increased particle size of 111.12 ± 1.24 nm, and a slightly higher zeta potential, indicating partial aggregation. These findings demonstrate that O. sanctum extract can effectively mediate the eco-friendly synthesis of stable silver nanoparticles, although their long-term stability is influenced by physicochemical interactions of surface biomolecules.